Kalindaqdaq in the tradition of "Sayyang Pattudu" in Polewali Mandar Regency - Rahmawati Harisa (Journal of Research and Multidisciplinary, 2021)
Kalindaqdaq in the tradition of "Sayyang Pattudu" which is one of the cultural products in Polewali Mandar Regency, South Sulawesi Province. Kalindaqdaq or Mandar poetry is oral literature because it is spoken orally. Kalindaqdaq is generally used during traditional events such as marriage, circumcision, or when parents give advice to their children. This study is an introduction to the Kalindaqdaq tradition to local culture and Islamic culture, the Islamic concept of acculturation, assimilation, diffusion, and integration and culture as a symbol system.